KENALI HIPERTENSI SEJAK DINI GUNA MENCEGAH KOMPLIKASI PADA ORANG TUA WALI SANTRI SDIT DARUL HIKMAH KRANGGAN SIDOHARJO SRAGEN - Sudaryanto, Sudaryanto; Sowwam, Muhammad (Nindikayla Institute, 2023)
One of the non-communicable diseases that is commonly found in the community is high blood pressure or often known as hypertension. At present hypertension is a national problem and even a global health problem. Not only in developing countries but also in developed countries. Hypertension is the entry point for various advanced diseases such as heart disease, kidney failure, diabetes mellitus and stroke (Ministry of Health of R Republic of Indonesia 2019). The 2013 Riskesdas results show a prevalence of hypertension of 25.8%, increasing to 34% in 2018, meanwhile the prevalence of hypertension in Central Java shows higher than the national rate of 69.4% in 2020, for Sragen Regency hypertension from a prevalence of 14.5 in 2017 increase to 25.6% in 2020 (BAPERIDA, 2022). The number of parents and guardians of students who do not know about hypertension yet and several guardians of students who suffer from hypertension at SDIT Darul Hikmah Sidoharjo Sragen are the main reason in the implementation of this program. The Health Education community service program “recognize hypertension early to prevent complications”aims to increase the knowledge of parents and guardians of students at SDIT Darul Hikmah Sidoharjo Sragen so that complications due to hypertension can be avoided. The result of this program is to increase the knowledge of parents and guardians of students at SDIT Darul Hikmah Sidoharjo Sragen